Generalized Coupled Fixed Point Results on Complex Partial Metric Space Using Contractive Condition (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we obtain coupled fixed point results on complex partial metric space under contractive condition. An example to support our result is presented.